Enhancement of postal code for addresses using / geocoding method and / coding model for mailing delivery / Nur Hazimah Nordin - Nordin, Nur Hazimah (2018)
Existing postal code system in Malaysia is too general and sometimes creating a confusion, not only for the residence but also organization that use postal code for mailing delivery. The aim of this study is to enhance the existing postal code system for addresses using coding model and geocoding method for mailing development of addressing system. Mukim of Kangar, Perlis was selected to conduct this study which is involving a development of a new coding model to generate a new postal code system of this particular area. Various data such as state, district, mukim and road data have been collected together with coding model parameters which is derived from extensive literature review from postal code of other countries. By using geocoding method, all these data will be processed using ArcGIS software. The outcome of the study is proposed the postal code for mailing address.. The proposed coding model is able to generate new postal code and assist user to find a location based on postal code. This result shows the suitability of coding model to the pilot study area, Kangar, Perlis.In conclusion, the enhancement in postal code is crucial for the development of addressing system and mailing delivery. Development of Malaysia is going on and a new postal code is providing not only for mailing delivery, but also health, economic, and industrial sector as well.